2021
DOI: 10.1186/s13046-021-01842-9
|View full text |Cite
|
Sign up to set email alerts
|

Targeting dopamine receptor D2 as a novel therapeutic strategy in endometrial cancer

Abstract: Background ONC201 is a dopamine receptor D2 (DRD2) antagonist that inhibits tumor growth in preclinical models through ClpP activation to induce integrated stress response pathway and mitochondrial events related to inhibition of cell growth, which is being explored in clinical trials for solid tumors and hematological malignancies. In this study, we investigated the anti-tumorigenic effect of ONC201 in endometrial cancer cell lines and a genetically engineered mouse model of endometrial cancer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 53 publications
2
15
0
Order By: Relevance
“…DRD2 Inhibition through genetic or pharmacological approaches has been shown to cause apoptosis and induce cell cycle arrest in leukemia, lung, colon, breast, endometrial, cervical, ovarian, pancreatic and brain cancer cells ( 11 , 12 , 35 40 ). ONC201 has recently been shown to induce apoptosis via targeting DRD2 in a wide variety of different cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DRD2 Inhibition through genetic or pharmacological approaches has been shown to cause apoptosis and induce cell cycle arrest in leukemia, lung, colon, breast, endometrial, cervical, ovarian, pancreatic and brain cancer cells ( 11 , 12 , 35 40 ). ONC201 has recently been shown to induce apoptosis via targeting DRD2 in a wide variety of different cancer types.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical studies have shown that ONC201 presents anti-tumorigenic effects in dopamine pathway-dysregulated solid tumors and hematologic malignancies ( 5 , 9 , 10 ). We recently found that ONC201 exhibited anti-tumorigenic and anti-metastatic activity in uterine serous carcinoma (USC) in vitro and inhibited tumor growth in a transgenic mouse model of endometrial cancer under obese and lean conditions ( 11 , 12 ). Phase I clinical trials revealed that ONC201 is clinically active and exceptionally well-tolerated with favorable pharmacokinetics and pharmacodynamics in a variety of cancers, including lymphoma, glioblastoma and endometrial cancer ( 4 , 11 , 13 16 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the molecules mediating the potential carcinogenicity of psychiatric drugs remain poorly understood. Neurotransmitter receptors, as frequent targets of psychiatric drugs, have been uncovered being relevant to tumorigenesis (13)(14)(15)(16)(17)(18)(19). Therefore, we hypothesized that the potential oncogenicity of psychotic drugs might be mediated by their targeted neurotransmitter receptors.…”
Section: Discussionmentioning
confidence: 99%
“…(12). Recent research has provided clues that genes commonly targeted by psychiatric drugs (neurotransmitter receptors) may play a role in the development of cancer (13)(14)(15)(16)(17)(18)(19), implying the potential oncogenic properties of antipsychotics may be related to the activity changes of these neurotransmitter receptors after drug administration. However, there are still very few studies disclosing the functions of neurotransmitter receptors in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies suggested that dopamine receptor D2 (DRD2) expression can be used to evaluate the prognosis of patients with gastric or esophageal cancer [49,50]. Moreover, targeting DRD2 has been a novel therapeutic strategy in tumor-related diseases [51][52][53]. us, DRD2 may play an important role in GC.…”
Section: Discussionmentioning
confidence: 99%